De novo mutations in idiopathic male infertility—A pilot study. (17th September 2020) - Hodžić, Alenka; Maver, Aleš; Plaseska‐Karanfilska, Dijana; Ristanović, Momčilo; Noveski, Predrag; Zorn, Branko; Terzic, Marija; Kunej, Tanja; Peterlin, Borut
Abstract: Study question: Are de novo mutations in the human genome associated with male infertility? Summary answer: We identified de novo mutations in five candidate genes: SEMA5A, NEURL4, BRD2, CD1D, and CD63 . What is known already: Epidemiological and genetic studies have consistently indicated contribution of genetic factors to the etiology of male infertility, suggesting that more than 1500 genes are involved in spermatogenesis. Study design, size, duration: First, we searched for de novo mutations in patients with idiopathic azoospermia with whole‐exome sequencing (WES). To evaluate the potential functional impact of de novo identified mutations, we analyzed their expression differences on independent testis samples with normal and impaired spermatogenesis. In the next step, we tested additional group of azoospermic patients for mutations in identified genes with de novo mutations. In addition to the analysis of de novo mutations in patients with idiopathic azoospermia, we considered other models of inheritance and searched for candidate genes harboring rare maternally inherited variants and biallelic autosomal and X‐chromosome hemizygous variants. Participants/materials, setting, methods: We performed WES in 13 infertile males with idiopathic azoospermia and their parents. Potential functional impact of de novo identified mutations was evaluated by global gene expression profiling on 20 independent testis samples. To replicate the results, we performed WES in further 16 independent azoospermic males, which were screened for the variants in the same genes. Library preparation was performed with Nextera Coding Exome Capture Kit (Illumina), with subsequent sequencing on Illumina HiSeq 2500 platform. Main results and the role of chance: We identified 11 de novo mutations in 10 genes of which 5 were considered potentially associated with azoospermia: SEMA5A, NEURL4, BRD2, CD1D, and CD63 . All candidate genes showed significant differential expression in testis samples composed of patients with severely impaired and normal spermatogenesis. Additionally, we identified rare, potentially pathogenic mutations in the genes previously implicated in male infertility—a maternally inherited heterozygous frameshift variant in FKBPL gene and inframe deletion in UPF2 gene, homozygous frameshift variant in CLCA4 gene, and a heterozygous missense variant NR0B1 gene, which represent promising candidates for further clinical implication. Limitations of the study, reasons for caution: We provided limited functional support for involvement of de novo identified genes in pathogenesis of male infertility, based on expression analysis. Additionally, the sample size was limited. Wider implications of the findings: We provide support that de novo mutations might contribute to male infertility and propose five genes as potentially implicated in its pathogenesis.